Structure-Based Drug Discovery - Jhoti, Harren; Leach, Andrew R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Discovering new medicines is becoming more challenging and the pharmaceutical industry is looking to new technologies to help in this mission. Structure-based drug discovery methods have been transformed in the last 5-10 years and are now having a major impact on the discovery of new drugs. Some of the most exciting developments in the field, such as Fragment-based methods, are described in this book. Structure-based drug discovery describes the latest developments in technologies that can be used to obtain the 3-D structures including the high profile structural genomics approaches being used worldwide. The use of 3-D protein structures in new, Fragment-based, approaches to drug discovery are described in some detail. This book includes experimental approaches using X-ray crystallography and NMR for Fragment-based screening as well as other biophysical methods for studying protein/ligand interactions. In addition, developments in computational chemistry methodology are covered together with an assessment of practical applications. This book is an invaluable resource for medicinal chemists in industry, computational chemists, drug discovery scientists and postgraduates in chemistry or structural biology.
Five Years of Increasing Structural Biology Throughput - A Retrospective Analysis -- Protein Production for Structural Genomics - Strategies for the Next Phase -- to Fragment Screening -- Fragment-Based NMR Screening in Lead Discovery -- Fragment-Based Screening by X-ray Crystallography -- Scaffold-Based Drug Discovery -- Biophysical Methods -- Illustration of Current Challenges in Molecular Docking -- Scoring Functions.
Keywords: CHEMISTRY; CHEMISTRY, PHYSICAL ORGANIC; BIOCHEMISTRY; PHARMACY; CHEMISTRY; MEDICINAL CHEMISTRY; BIOCHEMISTRY, GENERAL; PHARMACY; PHYSICAL CHEMISTRY; COMPUTER APPLICATIONS IN CHEMISTRY